Effect of cultivars and different weed management practices on yield, nutrient uptake and soil micro-flora in dry direct-seeded rice under coastal deltaic ecosystem - Pooja, K; Saravanane, P; Nadaradjan, S; Sundaravaradhan, S; Muthukumarasamy, S; Vijayakumar, S (ORYZA-An International Journal of Rice, 2021)
An experiment was conducted during September 2019 - January 2020 to investigate the effects of cultivars and different weed management practices on yield attributes, yield, nutrient uptake and soil micro-flora in dry direct-seeded rice (DDSR). Experiment was laid out in split plot design replicated thrice. The treatment combination consisted of three levels of cultivars in main plot (ADT 46, CO 52 and Improved white ponni) and five levels of weed management practices in the sub plots (application of pendimethalin @ 1 kg a.i ha-1 as preemergence herbicide at 3 days after sowing (DAS), bispyribac-sodium @ 0.02 kg a.i ha-1 as post-emergence herbicide at 20 DAS, sequential application of pendimethalin @ 1 kg a.i ha-1 followed by (fb) bispyribacsodium@ 0.02 kg a.i ha-1, hand weeding twice at 20 and 40 DAS and weedy check). Both the cultivars and weed management practices influenced the growth, nutrient uptake, soil microbial population and yield of the DDSR. However, the interaction did not influence any of the parameters significantly. Rice cultivar ADT 46 proved to be superior with respect to nutrient uptake and yield. Whereas, among weed management practices, the highest nutrient uptake and yield were obtained with sequential application of pendimethalin @ 1 kg a.i ha-1 fb bispyribac-sodium @ 0.02 kg a.i ha-1.